Enthalpy increments and redox thermodynamics of SrFeO3−δ. Issue 19 (14th October 2019) - Sereda, Vladimir; Sednev, Anton; Tsvetkov, Dmitry; Zuev, Andrey
Abstract: Abstract : Enthalpy increments, $Δ _{298}^T{H^0}$, for highly nonstoichiometric SrFeO3−δ (δ = 0.18–0.41) were obtained between 373 and 1273 K in air using drop calorimetry. The analysis of the $Δ _{298}^T{H^0}\left( T \right)$ dependence at lower temperatures allowed evaluating the enthalpy of tetragonal to cubic ${I4 / {mmm}} \, {\tf="TeX CM Bold Maths Symbols"\char33}\, Pm\bar{3}m$ phase transition at 560 K, 1.57 kJ/mol, and the Maier–Kelley function for $Δ _{298}^T{H^0}\left( T \right)$ of tetragonal SrFeO3−δ (space group ${I4 / {mmm}}$ ). Combined investigation of oxygen nonstoichiometry $\bolddelta \left( T \right)$ dependence, measured by thermogravimetry, and higher-temperature $Δ _{298}^T{H^0}\left( T \right)$ of cubic SrFeO3−δ (space group $Pm\bar{3}m$ ) yielded the temperature-dependent reduction (oxygen release) enthalpy, $Δ H_{{\rm{red}}}^{\rm{0}}$ . Calorimetrically-determined $Δ H_{{\rm{red}}}^{\rm{0}}$ of SrFeO3−δ increases from 65 ± 7 kJ/mol O at 873–973 K to 84 ± 7 kJ/mol O at 1073–1273 K, which may indicate that the short-range vacancy ordering in SrFeO3−δ is hampered at higher temperatures.